1311 FRAILTY IN RANDOMISED CONTROLLED TRIALS FOR DEMENTIA OR MILD COGNITIVE IMPAIRMENT. (16th January 2023) - Wightman, H; Quinn, T; Mair, F S; Lewsey, J; McAllister, D A; Hanlon, P
Abstract: Background: Frailty and dementia have a bidirectional relationship. However, frailty is rarely reported in clinical trials for dementia and mild cognitive impairment (MCI) which limits assessment of trial applicability. This study aims to use a frailty index (FI) to measure frailty using individual participant data (IPD) from clinical trials for MCI and dementia and to quality the prevalence of frailty and its association with serious adverse events (SAEs) and trial attrition. Methods: We analysed IPD from three dementia (n=1) and MCI (n=2) trials. An FI comprising physical deficits was created for each trial using baseline IPD. Poisson and logistic regression were used to examine associations with SAEs and attrition, respectively. Estimates were pooled in random effects meta-analysis. Analyses were repeated using an FI incorporating cognitive as well as physical deficits, and results compared. Results: The mean physical FI was 0.13 and 0.14 in the MCI trials and 0.25 in the dementia trial. Frailty prevalence (FI>0.24) was 5.1%, 5.4% in MCI trials and 55.6% in dementia. After including cognitive deficits, prevalence was similar in MCI (4.6% and 4.9%) but higher in dementia (80.7%). 99th percentile of FI (0.29 in MCI, 0.44 in dementia) was lower than in most general population studies. Frailty was associated with SAEs (physical FI IRR = 1.63 [1.43, 1.87]; physical/cognitive FI IRR = 1.67 [1.45, 1.93]). Frailty was not associated with trial attrition (physical FI OR = 1.18 [0.92, 1.53]; physical/cognitive FI OR = 1.17 [0.92, 1.49]). Conclusion: Measuring frailty from IPD in dementia and MCI trials is feasible. Severe frailty may be under-represented. Frailty is associated with clinically significant outcomes. Including only physical deficits may underestimate frailty in dementia. Frailty can and should be measured in trials for dementia and MCI, and efforts should be made to facilitate inclusion of people living with frailty.